1986
DOI: 10.1038/324549a0
|View full text |Cite
|
Sign up to set email alerts
|

Organ pipe radiant modes of periodic micromachined silicon surfaces

Abstract: In recent studies on small pyroelectric thermal anemometers with roughened surfaces we showed that one of the most widely used heat transfer models yielded calculated anemometer responses for flow and geometric behaviour that agreed functionally with observations, but were significantly smaller than the experimental data. As the first stage in investigating the role of small structures in heat transfer, we initiated a study of emittance from deep gratings. Here we report measurements at 400 °C of infrared (3 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(77 citation statements)
references
References 16 publications
1
75
0
Order By: Relevance
“…Thus, such a material is an example of a natural thermal source for which the field correlation in the source plane does not obey the scaling law established by Wolf [15]. Note that temporal and spatial coherence in thermal emission by silicon and SiC gratings has already been observed [5,6]. The analysis presented in this Letter explains the physical origin of this phenomenon.…”
Section: Rémi Carminati and Jean-jacques Greffetsupporting
confidence: 49%
See 1 more Smart Citation
“…Thus, such a material is an example of a natural thermal source for which the field correlation in the source plane does not obey the scaling law established by Wolf [15]. Note that temporal and spatial coherence in thermal emission by silicon and SiC gratings has already been observed [5,6]. The analysis presented in this Letter explains the physical origin of this phenomenon.…”
Section: Rémi Carminati and Jean-jacques Greffetsupporting
confidence: 49%
“…Nevertheless, recent interest in microscale and nanoscale radiative transfers [3], together with the development of local-probe thermal microscopy [4] and the observation of coherent thermal emission from doped silicon and silicon carbide (SiC) gratings [5,6], has raised new challenges. In fact, all these topics have in common the substantial role of the nonradiating (evanescent) thermal fields.…”
Section: Rémi Carminati and Jean-jacques Greffetmentioning
confidence: 99%
“…Hence, artificial materials with a structuredependent emissivity will also have a structure-dependent absorptivity. Hesketh et al 40 have demonstrated that the emissivity from deep surface gratings with a period comparable to the wavelength is different from the emissivity of a smooth surface. The emissivity was found to have a dependence on the grating period, which the authors attributed to standing wave modes generated in the deep gratings.…”
Section: Spectral Properties Of Infrared Materials: Bulkmentioning
confidence: 99%
“…In 1988, after a pioneering work of Hesketh et al 1 on the radiant modes of periodic micromachined silicon surfaces, the first thermal antenna has been designed using deep gratings. 2 Since then, numerous directional thermal sources and partially coherent sources have been proposed by texturing materials at subwavelength scale.…”
Section: Introductionmentioning
confidence: 99%